Sustainable Reuse of Dredged Soil as a Substrate Material by Improvement with Polyacrylamide, Straw, and Superabsorbent Polymer - Ling Mei; Yuxiang Chen; Lei Wang (Advances in Civil Engineering)
Every year, a significant quantity of dredged soil is generated as a result of channel dredging operations. However, there is relatively little evidence available regarding the sustainable reuse of dredged soils. In this study, an improved substrate material mainly composed of dredged soil was developed to examine the effects of three substrate amendments on the soil’s nutritional content, physical properties, and water retention capacity, as well as the germination rate of tall fescue. The orthogonal combination of the three substrates was controlled in a pot experiment using polyacrylamide (PAM), rice straw, and superabsorbent polymer (SAP) at application rates of 0.5, 1, 1.5, 2, and 2.5 g/kg; 15, 20, 25, 30, and 35 g/kg; and 0, 3, 6, 9, and 12 g/kg, respectively. The results showed that adequate application of PAM may improve the water retention capacity and available N retention capacity of dredged soil. PAM inhibited tall fescue germination significantly when the concentration exceeded 0.5 g/kg (p < 0.05). The addition of rice straw significantly improved the nutritional content of dredging soil and the germination rate of tall fescue (p < 0.05). Increased SAP significantly decreased the bulk density of dredged soil (p < 0.05). The lowest test group was 48.20% less than CK. This study offers novel ideas for the sustainable reuse of dredged soil and serves as a guide for future research aimed at increasing the effectiveness of external-soil spray seeding technologies.